2009
DOI: 10.2528/pierb08120406
|View full text |Cite
|
Sign up to set email alerts
|

Fast Analysis and Design of Frequency Selective Surface Using the Gmresr-FFT Method

Abstract: Abstract-In this paper, frequency selective surfaces (FSSs) are analyzed and designed. The analytical procedure is based on method of moments (MoM). The generalized minimal residual recursive method combined with fast Fourier transform (GMRESR-FFT) is utilized to accelerate the solution of the matrix equation. Our numerical results show that the GMRESR-FFT method can converge at least 3 times faster than the generalized minimal residual fast Fourier transform method (GMRES-FFT). In this paper, the cross dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The acceleration of electromagnetic numerical simulations based on the fast Fourier transform (FFT) algorithm has been presented recently [13][14][15]. In this paper, we have shown that the DGF method can be combined with FFT algorithms to increase its performance in modeling of planar antennas.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration of electromagnetic numerical simulations based on the fast Fourier transform (FFT) algorithm has been presented recently [13][14][15]. In this paper, we have shown that the DGF method can be combined with FFT algorithms to increase its performance in modeling of planar antennas.…”
Section: Introductionmentioning
confidence: 99%
“…A frequency‐selective surface (FSS) is typically made of dielectric substrates and conducting patches on or between the substrates 1–6. FSS structure has been intensively studied since the mid 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the FSS on the radome of the antenna in an aircraft is curved and finite extent. Spectral domain method of moment (MoM) is a popular technique for the analysis of infinite periodic FSS array 5–6. However, this method does not apply when the FSS structures are of finite sized or curve shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Integral equation (IE) is widely used for the numerical analysis of electromagnetic radiation and scattering [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Especially the time domain integral equation (TDIE) has been receiving much interest in studying many practical transient electromagnetic problems [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%